2013
DOI: 10.1074/jbc.m112.416578
|View full text |Cite
|
Sign up to set email alerts
|

Basal Splicing Factors Regulate the Stability of Mature mRNAs in Trypanosomes

Abstract: Background:Trypanosome trans-splicing depends on basal splicing factors such as U2AF35, U2FA65, and SF1. Results: Transcriptome analyses of RNAi-silenced cells of basal splicing factors reveal differential reliance on factors for trans-splicing and a role for the splicing factors in mRNA stability. Conclusion: Basal splicing factors regulate trans-splicing and mRNA stability. Significance: This is the first study to suggest that basal splicing factors regulate mRNA stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 74 publications
1
57
1
Order By: Relevance
“…It is also possible that there are SL sequences modified by nucleotide changes at some sites, or completely different SL sequences ligated to the transcripts (Zhang et al, 2013). Finally, the biological role of the 5 0 leader sequence in vivo has not been clearly established, although it may play a role in either the regulation of translation or mRNA stability (Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that there are SL sequences modified by nucleotide changes at some sites, or completely different SL sequences ligated to the transcripts (Zhang et al, 2013). Finally, the biological role of the 5 0 leader sequence in vivo has not been clearly established, although it may play a role in either the regulation of translation or mRNA stability (Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, we demonstrated that the trypanosome homologs of these proteins not only function in splicing, but also in mRNA stabilization. 27 U2AF35 was also shown to bind to ribosomes and to associate with factors involved in rRNA processing and ribosome assembly. 27 Three SR proteins were identified in T. brucei, TSR1, TSR1IP, and RRM1.…”
Section: -13mentioning
confidence: 99%
“…27 U2AF35 was also shown to bind to ribosomes and to associate with factors involved in rRNA processing and ribosome assembly. 27 Three SR proteins were identified in T. brucei, TSR1, TSR1IP, and RRM1. [28][29][30] TSR1 contains an RS domain at its C terminus and two RRM domains at its N terminus.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…Two life cycle stages are routinely cultured in the laboratory: the bloodstream form, which is similar to the forms that multiply in mammalian blood and tissue fluids, and the procyclic form, which is similar to the parasites in the tsetse fly midgut. Different mRNA levels-and also regulation during differentiation-are achieved by modulation of mRNA decay (17) and trans-splicing (18)(19)(20). Trypanosome mRNA decay pathways are similar to those of other eukaryotes: mRNAs are deadenylated by a CAF1-NOT complex (21), then the mRNA body is attacked from the 3= end by the exosome (22)(23)(24) and in the 5=-3= direction by XRNA (25).…”
mentioning
confidence: 99%